2022
DOI: 10.3390/diagnostics12081898
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Atrial Structure and Function by Echocardiography in Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is the most common arrhythmia with significant morbidity and mortality. Exacerbated by the aging population, the prevalence of AF is gradually increasing. Accurate evaluation of structure and function of left atrium (LA) has important prognostic significance in patients with AF. Echocardiography is the imaging technique of first choice to assess LA structure and function due to its better availability, accessibility and safety over cardiac computed tomography and cardiac magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…Furthermore, LA function can be assessed using tissue Doppler imaging (TDI) or speckle-tracking (ST) measurements of LA strain and strain rate [32]. However, the angle dependency of the method is a critical limitation of TDI-derived strain measurement [33]. If the angle of interrogation exceeds 20 degrees, the velocity could be underestimated.…”
Section: La Assessmentmentioning
confidence: 99%
“…Furthermore, LA function can be assessed using tissue Doppler imaging (TDI) or speckle-tracking (ST) measurements of LA strain and strain rate [32]. However, the angle dependency of the method is a critical limitation of TDI-derived strain measurement [33]. If the angle of interrogation exceeds 20 degrees, the velocity could be underestimated.…”
Section: La Assessmentmentioning
confidence: 99%
“…Echocardiography is the preferred modality for evaluating left atrial (LA) structure and function because it is more convenient, cost-effective, and safer than cardiac CT and MRI [ 7 ]. Multiple studies have identified that a larger LA diameter [ 16 , 17 , 18 , 19 ] and volume [ 7 , 15 , 20 , 21 ] measured via transthoracic echocardiography before CA are associated with a higher probability of AF recurrence. Moreover, the LA volume index, calculated by dividing LA volume by body surface area, including the maximum, mean, minimum, and volume index, was relevant to AF recurrence after CA [ 22 , 23 , 24 ].…”
Section: Use Of Echocardiography For the Prediction Of Af Recurrence ...mentioning
confidence: 99%
“…Studies have reported that increased EAT thickness measured using ultrasound is significantly associated with AF recurrence after CA and that this association is mainly related to pro-inflammatory cytokine release in EAT [ 23 , 29 , 30 ]. Moreover, speckle tracking echocardiography (STE) is an advanced, non-invasive echocardiographic technique independent of the angle of sound waves and has great potential for clinical application [ 7 ]. Nielsen et al .…”
Section: Use Of Echocardiography For the Prediction Of Af Recurrence ...mentioning
confidence: 99%
See 2 more Smart Citations